2011
DOI: 10.1097/dcr.0b013e31821c404a
|View full text |Cite
|
Sign up to set email alerts
|

Menopause and Obstetric History as Risk Factors for Fecal Incontinence in Women

Abstract: Complicated deliveries are risk factors for fecal incontinence in women. Fecal incontinence appears to be more prevalent in menopausal women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 30 publications
(39 reference statements)
0
10
0
Order By: Relevance
“…In a recent cross-sectional study, among 332 women, menopause was found to be an independent risk factor for FI, but the risk of FI did not increase among women aged 60 years and older. 24 FI was defined as involuntary leakage of stool and/or flatus, thus the results could be comparable to our definition of AI. However, the women were categorised as being incontinent if they had experienced symptoms within the past 4 weeks.…”
Section: Discussionmentioning
confidence: 63%
“…In a recent cross-sectional study, among 332 women, menopause was found to be an independent risk factor for FI, but the risk of FI did not increase among women aged 60 years and older. 24 FI was defined as involuntary leakage of stool and/or flatus, thus the results could be comparable to our definition of AI. However, the women were categorised as being incontinent if they had experienced symptoms within the past 4 weeks.…”
Section: Discussionmentioning
confidence: 63%
“…Obstetric factors are strongly associated with FI in women 54 and symptoms usually appear years later when aging and hormonal changes associated with menopause occur. 55 Large episiotomy, prolonged labor and use of forceps/spatula were factors much more prevalent in our patients compared with similar-aged HV. However, factors other than childbirth can be associated with FI.…”
Section: Discussionmentioning
confidence: 57%
“…had mild severity, scoring 0-5; 31.42%(55) reported moderate FI, scoring6-11; 47.42% (83) had severe FI, scoring 11-15 and finally, 14.28% (25) of the patients had very severe FI symptoms, scoring 16-20. According to FIQL score, incontinence reduced QoL especially in the coping and embarrassment subscales which decreased by nearly 50.00% Etiology of Fecal Incontinence: Obstetric and Coloproctological Risk Factors 2.29 ± 0.81 and 2.48 ± 0.83, respectively).…”
mentioning
confidence: 99%
“…our group did some previous studies focusing on hormonal changes and fi, mainly in menopause. 24,25 therefore we plan to investigate other stages of women's life that seem to be of paramount importance to the understanding of the development of functional bowel disorders. many factors have been described as contributors to pelvic floor disorders in pregnancy, including fi, such as increased abdominal pressure because of uterine volume and hormonal variations during pregnancy.…”
Section: Discussionmentioning
confidence: 98%